Examining geographic accessibility to radiotherapy in Canada and Greenland for indigenous populations: Measuring inequities to inform solutions. (May 2020) - Chan, Jessica; Friborg, Jeppe; Zubizarreta, Eduardo; van Eck, Jan Willem; Hanna, Timothy P.; Bourque, Jean-Marc; Gaudet, Marc; Dennis, Kristopher; Olson, Robert; Coleman, C. Norman; Petersen, Alice J.; Grau, Cai; et al.
Highlights: Geography is an important barrier to radiotherapy access for indigenous populations in Canada and Greenland. Geographic radiotherapy access is inequitable for indigenous populations in Canada. Geospatial analyses are important tools to highlight disparities in geographic access. Our geospatial analyses can inform solutions to improve geographic access. Abstract: Background: A high cancer burden exists among indigenous populations worldwide. Canada and Greenland have similar geographic features that make health service delivery challenging. We sought to describe geographic access to radiotherapy for indigenous populations in both regions. Methods: We used geospatial analyses to calculate distance and travel-time from indigenous communities in Canada and Greenland to the nearest radiotherapy center. We calculated the proportion of indigenous communities and populations residing within a 1 and 2-hour drive of a radiotherapy center in Canada, and compared the proportion of indigenous versus non-indigenous populations residing within each drive-time area. We calculated the potential distance and travel-time saved if radiotherapy was available in northern Canada (Yellowknife and Iqaluit), and Greenland (Nuuk). Results: Median one-way travel from indigenous communities to nearest radiotherapy center in Canada was 268 km (3 h when considering any transportation mode), and 4111 km (6 h by plane) in Greenland. In Canada, 84% and 68% of indigenous communities were outside a 1 and 2-hour drive from a radiotherapy center, respectively. Only 2% of the total population in Canada resided outside a 2-hour drive from a radiotherapy center. However, indigenous peoples were 336 times more likely to live more than a 2-hour drive away, compared to non-indigenous peoples. Nearly 3 million km and 4000 h of travel could be saved over a 10-year period for patients with newly diagnosed cancers in Canada, and 7 million km and 10, 000 h in Greenland, if radiotherapy was available in Yellowknife, Iqaluit and Nuuk. Conclusions: Geography is an important barrier to accessing radiotherapy for indigenous populations in Canada and Greenland. A significant disparity exists between indigenous and non-indigenous peoples in Canada. Geospatial analyses can help highlight disparities in access to inform radiotherapy service planning.